Evaluasi Tingkat Pengetahuan Masyarakat Mengenai Penggunaan Antibiotik Pre dan Post Penyuluhan di Desa Dolok Nagodang, Kecamatan Uluan, Kabupaten Toba - Gultom, Parulian Dormaida; Ginting, Ferawati; Pakpahan, Melanie (Herbal Medicine Journal, 2025)
Inappropriate use of antibiotics in the society has been a major driver to antimicrobial resistance (AMR) in the world, specifically in low- and middle-income countries. Many studies have observed that the lack of community awareness and adequate knowledge about antibiotics may lead to their inappropriate use. This research aimed to describe a situation of the level of knowledge and understanding of community in Dolok Nagodang Village, Uluan District regarding the use of antibiotics pre and post health education. This study provided further insight into the proper and rational use of antibiotics, to reduce the occurrence of antibiotic resistance. This research utilized a quantitative descriptive method with a sample of 77 respondent sselected through purposive sampling. Data analysis in this research involved organizing data into tables (tabulation) to summarize frequencies and then calculating percentages to express those frequencies relative to the total. Scoring for each answer from the questionnaire is processed based on the Guttman Scale. The results revealed a significant increase in the percentage of individuals with a good understanding after health education was implemented. Pre-health education showed 45.45% with a good level of knowledge, while post-health education saw this increase to 93.50%. This indicates the effectiveness of health education in improving the community knowledge about antibiotics use.